Co-treatment of Pitavastatin and Dexamethasone Exacerbates the High-fat Diet–induced Atherosclerosis in apoE-deficient Mice. Issue 2 (August 2015) - Zhang, Wenwen; Wang, Xue; Hu, Wenquan; Liu, Lipei; Li, Xiaoju; Han, Jihong; Chen, Yuanli; Duan, Yajun
Abstract : Abstract: Activation of macrophage adipocyte fatty acid-binding protein (FABP4) induces development of atherosclerosis in animal models. We previously reported that statin inhibited while dexamethasone activated macrophage FABP4 expression. However, co-treatment of macrophages with statin and dexamethasone induced FABP4 expression in a synergistic manner, which implies that this co-treatment may exacerbate high-fat diet (HFD)–induced atherosclerosis. In this study, we fed apoE-deficient (apoE −/− ) mice with HFD or HFD containing dexamethasone or pitavastatin or both for 16 weeks. Compared with HFD alone, pitavastatin or dexamethasone had little effect on lesions in both en face aortas and aortic root cross sections. However, the co-treatment exacerbated HFD-induced lesions. In addition, the co-treatment decreased collagen content and disturbed the integrity of lesion caps. Both serum total cholesterol and LDL cholesterol levels were reduced by pitavastatin and increased by dexamethasone, respectively. However, the co-treatment had little effect on both total cholesterol and LDL cholesterol levels, indicating that the exacerbation of lesions is independent of total cholesterol or LDL cholesterol levels. FABP4 expression in aortic lesion area was significantly induced by the co-treatment, suggesting that activation of FABP4 expression is a main contributor to lesions. In conclusion, our study demonstrates that co-treatment of pitavastatin and dexamethasone exacerbates HFD-induced atherosclerosis and defines a potential risk to use the dual treatment for patients in clinics.